Design and Implementation of a Simple Online Court Case Management System Based on the Android Platform - Ali, Chawan Taha Hama; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2020)
The main purpose of this research is to create a new application in Android Operating System for a complainant who cannot visit his/her lawyer regularly or unable to go out due to fear of his/her life. Thanks to this research, a new application was established to make a bridge between a complainant and his/her lawyer. Everything is done automatically after necessary data entered into the application. So, costs are reduced and wasting of the time is diminished. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: application; court; lawyer user; system